The Assessment of Carbon Dioxide Automated Angiography in Type II Endoleaks Detection: Comparison with Contrast-Enhanced Ultrasound. (26th March 2018) - Mascoli, Chiara; Faggioli, Gianluca; Gallitto, Enrico; Vento, Vincenzo; Indelicato, Giuseppe; Pini, Rodolfo; Vacirca, Andrea; Stella, Andrea; Gargiulo, Mauro
Abstract : Introduction . Iodinated contrast media completion angiography (ICM-A) may underestimate the presence of type II endoleak (ELII) after endovascular aortic repair (EVAR), particularly if they are at low flow. Contrast-enhanced ultrasound (CEUS) has been proposed as the gold standard in ELII detection during EVAR follow-up. Intraprocedural carbon dioxide (CO2 ) angiography has been shown to be useful in this setting; however no comparative studies including these three techniques are currently available. Our aim was to investigate the accuracy of a new automated CO2 angiographic (CO2 -A) system in the detection of ELII, by comparing it with ICM-A and CEUS. Methods . A series of consecutive patients undergoing EVAR for abdominal aortic aneurysm (AAA) were enrolled and submitted to ICM-A and CO2 -A during the procedure. The iodinated contrast media were delivered through an automatic injector connected to a pigtail catheter in the suprarenal aorta. CO2 was delivered through a recently available automatic injector connected to a 10 F sheath positioned in the external iliac artery. All patients were blindly evaluated by CEUS within postoperative day 1. The ICM-A and CO2 -A ability to detect ELII was compared with that of CEUS through Cohen's concordance Index( K ) . Results . Twenty-one patients were enrolled in the study. One (5%), seven (33%), and four (19%) ELII were detected by ICM-A, CO2 -A, and CEUS, respectively. The only ELII detected by ICM-A was also detected by CO2 -A and CEUS. Three cases of ELII detected by CO2 -A were not detected by CEUS. All ELII detected by CEUS were visualized by CO2 -A. CEUS and ICM-A showed a poor agreement (Cohen'sK : 0.35) while CEUS and CO2 -A showed a substantial agreement (Cohen'sK : 0.65) for ELII detection. Conclusion . CO2 -A is safe and effective method for ELII detection in EVAR, with a significantly higher agreement with CEUS if compared with ICM-A. This trial is registered with 155/2015/U/Oss.